Silencing the Sea : Secular Rhythms in Palestinian Poetry. - Furani, Khaled (Stanford University Press, 2012)
Silencing the Sea follows Palestinian poets' debates about their craft as they traverse multiple and competing realities of secularism and religion, expulsion and occupation, art, politics, immortality, death, fame, and obscurity. Khaled Furani takes his reader down ancient roads and across military checkpoints to join the poets' worlds and engage with the rhythms of their lifelong journeys in Islamic and Arabic history, language, and verse. This excursion offers newfound understandings of how today's secular age goes far beyond doctrine, to inhabit our very senses, imbuing all tha.